2020
DOI: 10.1017/s1368980019004798
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and its relation to dietary patterns among a selected urbanised and semi-urbanised Tibetan population in transition from nomadic to settled living environment

Abstract: Objective: To explore the scope of metabolic syndrome (MetS) and its relationship to the major dietary patterns among an urbanised and semi-urbanised Tibetan population in transition from nomadic to settled settings. Design: Cross-sectional. Setting: Community-based. Participants: Urbanised and semi-urbanised Tibetan adults (n 920, aged 18–90 years), who have moved from nomadic to settled living environments, answered questionnaires on food consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Current evidence has shown the roles of dietary factors and the diagnostic criteria of diabetes. Our study has identified the metabolic protective role of traditional Tibetan diets, in which tsamba, a whole grain rich in β glucagon functioning in glucose regulation, is an important component [ 6 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current evidence has shown the roles of dietary factors and the diagnostic criteria of diabetes. Our study has identified the metabolic protective role of traditional Tibetan diets, in which tsamba, a whole grain rich in β glucagon functioning in glucose regulation, is an important component [ 6 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the mortality rates in cardiovascular diseases and diabetes in China in 2018 were 364.6 and 19.1 per 100,000, respectively, based on a recent national report [ 5 ]. In addition, recent epidemiological studies in different settings have revealed an unexpectedly high prevalence of obesity and related NCDs [ 6 , 7 , 8 ]. Nevertheless, the obesity and NCD patterns among the overall Tibetan populations were understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Total weekly intake was endowed with the scores of 0, 1, 2, and 3 according to the classification as never, low, medium, and high. To obtain the combined effect of Tsampa, butter tea, and Qing cha on MetS, these numbers were added together ranging from 0 to 9, and then divided into four categories: never/rarely (0-2), low score (3-5), middle score (6, 7), and high score (8,9). To examine the potential effect modification between the consumption of each food, we tested models with interaction terms.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited studies regarding the association between dietary patterns in Tibet and MetS with inconsistent results. One study reported a null association between the risk of MetS and the traditional Tibetan and urbanized diet, while another showed that urban dietary pattern was a risk factor for MetS, both of which had small sample sizes and defects in research design with inadequate control of confounding factors (7,8). Further, due to different dietary assessment items, different definitions of MetS [e.g., ATP III vs. International Diabetes Federation (IDF)], and different populations investigated, it is difficult to directly compare the effects of the Tibetan diet on MetS from various studies.…”
Section: Introductionmentioning
confidence: 99%
“…The meeting outcomes also concluded that the presence of three out of five risk factors would diagnose MetS, with the five criteria being elevated blood pressure, central obesity, elevated TG, elevated FBG, and reduced HDL [ 14 ]. MetS and its relation to dietary patterns were recently studied, and it was concluded that nutrition interventions need to be tailored to address the MetS occurrence in various ethnic groups [ 15 ].…”
Section: Introductionmentioning
confidence: 99%